Evaluation of Strategic Responses to Institutional Pressures for CSR in the Clothing Industry: A Case Study of MSMEs in the UK - Basera, Anshuja (2015)
This dissertation aims to identify what strategies businesses employ in response to institutional pressures for undertaking corporate social responsibility (CSR). Relevant literature on CSR, stakeholder and strategy are reviewed to find the answer. An analytical framework is developed based on the conceptual framework of Institutional theory of Isomorphic change and Antecedents of Strategic Responses to Institutional Pressures in conjunction with the statistical concept of Moderated-mediation or conditional indirect effects. This framework is used to analyse case studies of six micro, small and medium sized enterprises in the UK clothing industry. The findings reveal a diverse range of strategic responses of the MSME’s and explain the role of the predictive factors in moderating those strategic responses to institutional pressures for CSR.